Baseline data for Yemen School Milk Initiative Study - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
IFPRI, in collaboration with implementation partners HSA Group and World Food Programme, evaluated the impact of adding a milk intervention to a micronutrient fortified school feeding program. The study is a cluster randomized control trial (cRCT) that took place in 42 schools in Al Mukha district, Yemen. The evaluation includes baseline surveys with households and schools conducted before implementing the milk intervention (November-December 2023), and endline surveys conducted with the same households and schools after the interventions (April-May 2024). These datasets are with respect to the baseline surveys and contains baseline household and school data. The first part comprises household-level modules such as household roster, housing, assets, food security, and occurrence of shocking events. The second part comprises individual-level modules administered to children receiving the program, which include nutritional status, diet, health, cognition, and learning. The last part includes the school level modules such as infrastructure and food environment, administered to school staff.